Scrivere e descrivere: La pervasività dell’ekphrasis nella poesia di Edoardo Sanguineti - Verdone, Alessio (Italianistica Debreceniensis, 2021)
This paper aims to explore the all-pervasiveness of the technique of ekphrasis within Edoardo Sanguineti’s poetry, from Laborintus (1956) to Varie ed eventuali (2010). The study is conducted looking at six exemplary texts (Laborintus 3 and 7, Reisebilder 14, Cataletto 1, Corollario 43, Mantova 15) belonging to different periods of Sanguineti’s literary career and comparing them with the visual objects that they describe. In this way, the study tries to show the usage of ekphrasis not only as a simple rhetorical device but also as a primary poetical tool. Finally, the article drafts some future ways for further investigation, such as the cataloguing of all the ekphrasises hidden in Edoardo Sanguineti’s poetry, the application of the theoretical results achieved by the international visual studies, and the possibility of connecting Sanguineti’s ekphrasis with the ones used by other Italian contemporary poets.